Blood in the dust - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Hunter Buchanon, 2021)
"When the Civil War ended, Hunter Buchanan and his coyote sidekick Bobby Lee forged a new life in the Black Hills, Dakota. Now they'll have to fight to the death to keep it . . . THERE'S COYOTES IN THEM THERE HILLS. Ex-Rebel tracker Hunter Buchanan is down on his luck. He lost his family's ranch in a fire. He lost his gold to a thief. And he just might lose his fiancee--a beautiful saloon girl named Annabelle--to a stinking-rich rival. But Hunter's not ready to give up just yet. He's got a temporary sheriff's badge, a long-range plan to rebuild his ranch, and his loyal coyote Bobby Lee by his side to make things right. Too bad it all goes wrong--when Annabelle gets kidnapped . . . The mayhem begins with a stagecoach robbery in the Black Hills town of Tigerville. It won't end until Sheriff Hunter Buchanan gets back his girl and his gold--on a long, dusty trail of bloodsoaked vengeance . . ."--Provided by publisher.